5PSQ-072 Acute promyelocytic leukaemia after infliximab therapy in a crohn's disease patient: a case report and a review of the literature. (March 2019) - Camuffo, L; Lucatelli, MV; Pieri, G; Bacci, C; Inzalaco, G; Puzziferri, R; Di Carlo, C; Fazio, M
Abstract : Background: In the post-marketing setting, only cases of leukaemia have been reported in patients treated with infliximab. There is also an increased background risk for lymphoma and leukaemia in patients with long-standing, highly active, inflammatory disease, which complicates risk estimation. Purpose: We wanted to report a case of acute promyelocytic leukaemia (APL) in a patient with Crohn's disease (CD) after infliximab therapy. We also reviewed the available literature. Material and methods: In June 2018 the patient's data were collected from the electronic medical records (Whospital) in our hospital: the literature was reviewed using the Pubmed database. Results: A 50 years' old male, with perianal CD since 2000, was diagnosed with APL in March 2018 after a bone marrow biopsy for grade 3/4 neutropaenia during an episode of pulmonary embolism and deep vein thrombosis. Infliximab therapy began in 2003 and was intermittent, with discontinuation in 2004 and 2006 because of good therapy response. He was unresponsive to these prior therapies: steroids, azathioprine and adalimumab. In 2015 he was enrolled for a few months, without good response, in a clinical trial with ustekinumab. After APL diagnosis, infliximab was discontinued and induction therapy for APL with arsenic trioxide and tretinoin (ATO +ATRA) was started. Remission began in April 2018, maintenance ATO +ATRA therapy was started and was still continuing in June 2018. The review of the literature found five reports of leukaemia cases after infliximab therapy in patients with CD (three), rheumatoid arthritis (one) and ankylosing spondylitis (one); three were males and two were females; the mean age of the patients was 46. The review also showed a higher risk of the occurrence of malignancies in patients on immunosuppressive therapy and/or with autoimmune/inflammatory disorders. Conclusion: Our patient presented APL after a long exposure to infliximab, which raises the concern that infliximab may be involved in leukaemia development. The presence of an autoimmune disease, such as CD, and prior immunosuppressive therapies, such as azathioprine and TNF-alfa inhibitors, may also have caused the development of leukaemia. Risk estimation is difficult. However, we suggest prompt evaluation for patients who develop haematological abnormalities when treated with infliximab. References and/or acknowledgements: No conflict of interest.